Kemampuan Guru Sosiologi dalam Pengembangan Pembelajaran Berbasis Online Masa Pandemi Covid-19 di Kabupaten Sumbawa Barat - Esha Qaumil Jannah; Sukardi Sukardi; Masyhuri Masyhuri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to identify the capability of sociology teachers in developing online-based learning during the Covid-19 pandemic in the West Sumbawa Regency based on various variables. This study used a quantitative approach with a survey method. The entire statistical population in this study were senior high school students in West Sumbawa Regency. The sample in this study used the solving formula so that a sample size 317 was obtained. The data was collected through a google form-assisted questionnaire as well as through the interview method and then analyzed quantitatively using comparative analysis. The result showed that the capability of sociology teachers in developing online-based learning during the Covid-19 pandemic is categorized as sufficient. The capability of teachers in developing online-based learning is not different from the teacher status variable but differs based on the location of the school. Teachers outside the district city are better than those in the city. An important implication is that teachers are expected to be more active in seeking information about the development of online-based learning and using the latest technological facilities and infrastructure.